Construction efficiency of shield tunnelling through soft deposit in Tianjin, China. (June 2021) - Yan, Tao; Shen, Shui-Long; Zhou, Annan; Lyu, Hai-Min
Highlights: Key factors related to construction efficiency during shield tunnelling are identified. Relationship between cutterhead torque and fine-particle content is obtained. A function between cutterhead torque and total energy consumption is obtained. Relationship between total energy and soil particle gradation is obtained. Soil characteristics ahead of cutterhead of shield tunnelling can be determined. Abstract: This study presents a case study on construction efficiency during earth pressure balance (EPB) shield tunnelling in the soft deposit of Tianjin, China. To evaluate the construction efficiency, energy consumption during tunnelling is summarised and soil properties are analysed in terms of several key factors related to energy consumption during the tunnelling process. Energy consumption is a key indicator of costs for EPB shield tunnelling. Based on monitoring data from Tianjin Metro Line No. 5, the K-means clustering algorithm is adopted for soil property analysis. The analysed results indicate that the energy consumption of a cutterhead comprises more than half of the total energy consumption during tunnelling. The obtained relationship between the torque of the cutterhead and total energy consumption can be used to enhance construction efficiency. The torque of the cutterhead can be expressed using the fine-particle content. Consequently, the total energy consumption of the shield tunnelling machine can also be estimated according to the particle size distribution of the soils. The results of this case study will be helpful for improving the construction efficiency of EPB shields.